Numeral Classifier Bahasa Bali: Suatu Kajian Tipologi Linguistik - Dwi Mahendra Putra; I Putu Permana Mahardika; Ni Made Ayu Susanthi Pradnya Paramitha; Ni Made Ari Dwijayanthi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This research is an of intralingual typology in the form of a numeral classifier in Balinese. The main theory used in this research was the theory of classifier proposed by Aikhenvald (2000). The data was collected by the observation method. Meanwhile, the data were analyzed by grouping the obtained data into the types of numeral classifier proposed by Aikenvald (2000) and Lyons (1977). Based on the result of data analysis, there are types of numeral classifiers of the Balinese, namely the individual, the size, the volume, and the hour numeral classifier. The individual classifier used for count individual object which consisting of bidang, bungkul, ijas, tukel, ukud. The size of a numeral classifier can be stated with fingers and a human hand. The volume numeral classifier used for unit mass measurement, such as catu, cééng, and céntong. The hour numeral classifier used for to stated dauh ‘hours’, which consisting of dauh pisan, dauh ro, dauh tiga.